A Merchant Bank's Overview of Mineral Valuation Methodologies - Harper F (The Australasian Institute of Mining and Metallurgy, 1994)
This paper outlines the authors' views of the methodologies which can be employed to value mineral properties at different stages of development for the purposes of project financing, mergers and public floats. This paper discusses the key issues in Discounted Cash Flow (DCF) analysis including the importance of data verification and the shortcomings in DCF analysis. Stockmarket valuation measures and valuation methodology for exploration and pre development projects are examined through examples and pitfalls are identified. The use of valuations in corporate transactions and their strategic value is also discussed.